2013
DOI: 10.1038/tp.2013.79
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anxiety and infants' hippocampal development: timing matters

Abstract: Exposure to maternal anxiety predicts offspring brain development. However, because children's brains are commonly assessed years after birth, the timing of such maternal influences in humans is unclear. This study aimed to examine the consequences of antenatal and postnatal exposure to maternal anxiety upon early infant development of the hippocampus, a key structure for stress regulation. A total of 175 neonates underwent magnetic resonance imaging (MRI) at birth and among them 35 had repeated scans at 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
182
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(208 citation statements)
references
References 53 publications
10
182
1
6
Order By: Relevance
“…The result is for a potential fetal glucocorticoid overexposure to impact ongoing developmental events including a restriction of fetal growth, premature maturation of proliferative neural precursors, and altered HPA axis development (Seckl and Holmes, 2007). Notably, these predicted effects are consistent with the reduced perinatal brain volumetric findings in association with maternal stress described earlier (Li et al, 2012;Lou et al, 1994;Qiu et al, 2013). In addition to the potential for actions of excess glucocorticoids on the developing fetal brain, excess glucocorticoids also act within the placenta to have an impact on endocrine functions, thus compromising placental growth, vascularization, and nutrient transport (Hewitt et al, 2006;Wyrwoll et al, 2009).…”
Section: Transplacental Barrier Permeabilitysupporting
confidence: 65%
See 1 more Smart Citation
“…The result is for a potential fetal glucocorticoid overexposure to impact ongoing developmental events including a restriction of fetal growth, premature maturation of proliferative neural precursors, and altered HPA axis development (Seckl and Holmes, 2007). Notably, these predicted effects are consistent with the reduced perinatal brain volumetric findings in association with maternal stress described earlier (Li et al, 2012;Lou et al, 1994;Qiu et al, 2013). In addition to the potential for actions of excess glucocorticoids on the developing fetal brain, excess glucocorticoids also act within the placenta to have an impact on endocrine functions, thus compromising placental growth, vascularization, and nutrient transport (Hewitt et al, 2006;Wyrwoll et al, 2009).…”
Section: Transplacental Barrier Permeabilitysupporting
confidence: 65%
“…These studies reported delayed overall brain growth, limbic systemspecific volumetric changes, and white matter abnormalities (Li et al, 2012;Lou et al, 1994;Qiu et al, 2013Qiu et al, , 2015Rifkin-Graboi et al, 2013). Such early observations appear to persist into childhood and adolescence, are correlated with affective problems, and may contribute to symptoms in patients with schizophrenia and autism (Buss et al, 2010(Buss et al, , 2012Davis et al, 2013;Du et al, 2013;Sarkar et al, 2014;Zikopoulos and Barbas, 2010).…”
Section: Reprogramming In the Prenatally Stressed Brainmentioning
confidence: 97%
“…Because maternal mood generally remains stable across the peripartum period, the Lupien et al (3) findings might reflect a prenatal maternal mood, thus resolving the apparent contradiction. In support of this idea, postnatal maternal mood, controlling for prenatal mood, predicts hippocampal growth trajectories (11). Similarly, prenatal maternal cortisol levels associate with the amygdala but not hippocampus volume in middle childhood (10).…”
Section: Sensitive Periodsmentioning
confidence: 86%
“…A separate study similarly observed an effect of prenatal maternal anxiety on neonatal frontal cortical thickness that was moderated by functional variants of the catechol-O-methyltransferase (COMT) gene, which regulates catecholamine signaling and is implicated in anxiety, pain, and stress responsivity (Qiu et al, 2014). Furthermore, a strong positive association was observed between postnatal maternal anxiety and offspring right hippocampal growth and a strong negative association between postnatal maternal anxiety and offspring left hippocampal volume at 6 months of age (Pruessner et al, 2008;Qiu et al, 2013). Notably, the frontal cortex and hippocampus have been implicated in fear and stress reactivity, trait anxiety, and psychopathology, including PTSD (Rusch et al, 2001;Shin et al, 2006;Pruessner et al, 2008).…”
Section: Neuroanatomicalmentioning
confidence: 95%